2018
DOI: 10.1113/ep086867
|View full text |Cite
|
Sign up to set email alerts
|

The inspired sine‐wave technique: A novel method to measure lung volume and ventilatory heterogeneity

Abstract: The inspired sine-wave technique (IST) is a new method that can provide simple, non-invasive cardiopulmonary measurements. Over successive tidal breaths, the concentration of a tracer gas (i.e. nitrous oxide, N O) is sinusoidally modulated in inspired air. Using a single-compartment tidal-ventilation lung model, the resulting amplitude/phase of the expired sine wave allows estimation of end-expired lung volume (ELV), pulmonary blood flow and three indices for ventilatory heterogeneity (VH; ELV /FRC , ELV /FRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
(60 reference statements)
1
17
1
Order By: Relevance
“…IST measurements of absolute ELV are below those measured by SF 6 and CT by 12e13% and do not fall within 5% of the reference method recommended by the European Respiratory Society/American Thoracic Society consensus statement. 33 These results are consistent with a previous study of IST, in which Bruce and colleagues 17 showed that IST underestimated functional residual capacity (FRC) by 32% (1080 ml) compared with body plethysmography in humans, where the mean FRC was 3.4 L. The underestimation was smaller in our study, with a mean bias of e12 to e13% (e129 to e161 ml), where the overall mean ELV was 809 ml. IST measures the volume of ventilated regions of the lung, and it is expected that IST will underestimate lung volume compared with CT, which estimates the entire thoracic gas volume.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…IST measurements of absolute ELV are below those measured by SF 6 and CT by 12e13% and do not fall within 5% of the reference method recommended by the European Respiratory Society/American Thoracic Society consensus statement. 33 These results are consistent with a previous study of IST, in which Bruce and colleagues 17 showed that IST underestimated functional residual capacity (FRC) by 32% (1080 ml) compared with body plethysmography in humans, where the mean FRC was 3.4 L. The underestimation was smaller in our study, with a mean bias of e12 to e13% (e129 to e161 ml), where the overall mean ELV was 809 ml. IST measures the volume of ventilated regions of the lung, and it is expected that IST will underestimate lung volume compared with CT, which estimates the entire thoracic gas volume.…”
Section: Discussionsupporting
confidence: 92%
“…IST uses commercially available components commonly used in anaesthetic/intensive care practice, and has proven efficacy in spontaneously ventilating healthy volunteers. 17,18 To date, IST's ability to measure ELV in mechanically ventilated lungs has not been tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the IST and inspired sinewave device (ISD) have been detailed elsewhere, 15 but in brief: at the start of each inhalation a small volume of N 2 O is injected into inspired gas by a mass flow controller (Alicat Scientific, Inc., Tucson, AZ, USA). Airflow is measured using an ultrasonic flowmeter (VenThor 22/2A; Thor Laboratories, Budapest, Hungary), and N 2 O concentration using a rapid mainstream infrared sensor (Square One Technology, Boulder, CO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…S1.
Fig 1A typical example of recorded data, with inspired N 2 O concentration oscillating sinusoidally around a fixed mean (4%), with a predetermined amplitude (3%) and period (180 s). Green line is the expired N 2 O concentration; the blue and red crosses are the N 2 O concentrations in inspired gas and end-tidal gas, respectively; the blue and red lines are the inspired and expired N 2 O sinewaves, respectively (reproduced from Bruce and colleagues 15 ).
…”
Section: Methodsmentioning
confidence: 99%